TINGKAT SELF-EFFICACY DAN TINGKAT SELF-REGULATED LEARNING MAHASISWA PRODI PGMI FAKULTAS TARBIYAH DAN KEGURUAN UIN SUNAN AMPEL SURABAYA - Sihabudin, Sihabudin (Journal Of Islamic Elementary School (JIES), 2018)
The research type is Survey. This research was implemented in Education and Teaching Faculty of Sunan Ampel Islamic State University. The population of this research is all active regular program students of PGMI Department of Education and Teaching Faculty of Sunan Ampel Islamic State University amount to 492 students. Sampling technique that was used at this research is proportional cluster random sampling. The amount of students sample that be used on this research is 221 students. Data collecting techniques that be used on this research are documentation and questionare. Data analysis technique that be used on this research is descriptive statistic analysis. The results of this research are: 1) There are 38 (17,20%) students of PGMI Department of Education and Teaching Faculty of Sunan Ampel Islamic State University those who have very high level of self-efficacy, 47 students (21,27%) those who have high level of self-efficacy, 106 students (47,96%) those who have low level of self-efficacy, and 30 students (13,57%) those who have very low level of self-efficacy, So, majority of PGMI students have lower believe and judgement to their self-efficacy. 2) There are 35 (15,85%) students of PGMI Department of Education and Teaching Faculty of Sunan Ampel Islamic State University those who have very high level of self-regulated learning, 73 students (33%) those who have high level of self-regulated learning, 80 students (36, 21%) those who have low level of self-regulated learning, and 33 students (14,94%) those who have very low level of self-regulated learning . Thats, Majority of PGMI students have low ability to organize and axecute their learning process.